2021
DOI: 10.1186/s12882-021-02612-7
|View full text |Cite
|
Sign up to set email alerts
|

Association between the psoas muscle index and hospitalization for pneumonia in patients undergoing hemodialysis

Abstract: Background Although muscle mass loss and pneumonia are common and crucial issues in hemodialysis (HD) patients, few reports have focused on their association, which remains unclear. This study assessed the association between skeletal muscle mass and the incidence of pneumonia in HD patients using the psoas muscle index (PMI). Methods This retrospective study included 330 patients on HD who were treated at a single center between July 2011 and June… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Given that the serum creatinine level was significantly lower in both the MCI and suspected dementia groups than in the normal group, cognitive dysfunction may be associated with loss of muscle mass. Moreover, muscle mass loss is associated with mortality in patients undergoing hemodialysis 13,26,27 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that the serum creatinine level was significantly lower in both the MCI and suspected dementia groups than in the normal group, cognitive dysfunction may be associated with loss of muscle mass. Moreover, muscle mass loss is associated with mortality in patients undergoing hemodialysis 13,26,27 …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, muscle mass loss is associated with mortality in patients undergoing hemodialysis. 13,26,27 Malnutrition, which is an important aspect of frailty, is associated with cognitive impairment in patients undergoing hemodialysis. 23 Based on logistic regression analysis in this study, GNRI has a negative impact on cognitive function.…”
Section: Discussionmentioning
confidence: 99%
“…One aspect is low BMI as a cause of poor feeding status; BMI is related with swallowing function that is associated with muscle mass. Previous studies have suggested that patients undergoing hemodialysis tend to lose their muscle mass, which leads to weakened swallowing function [20][21][22]. A decrease in muscle mass results in weakness [23] and loss of mobility [24]; these changes can negatively correlate with the effective flow of swallowed materials [2].…”
Section: Plos Onementioning
confidence: 99%